Implementation of Playing Methods in Learning Science in Improving Children's Critical Thinking Ability in Raudhatul Athfal Assyifa Medan - Rafida, Tien; Harahap, Mariani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study was to determine: (1) the implementation of playing methods in science learning at Raudhatul Atfhal Asyyifa Medan. (2) children's activities in participating in science learning at Raudhatul Atfhal Asyyifa Medan, and (3) the application of play methods can improve children's critical thinking skills in science learning. The study was conducted at Raudhatul Atfhal Asyyifa Medan. The method used is a qualitative research method. Data sources are the principal, teachers and students. Data retrieved through observation, documentation, and interviews. Data are analyzed based on data reduction, data presentation, and conclusions. The research findings show: (1) the implementation of play methods in science learning at Raudhatul Atfhal Asyyifa Medan, presented through various science experiment activities that can improve children's critical thinking skills. This can happen, because in science learning done with fun through science experiments that are packaged in playing while learning, children are not burdened with things that are academic because actually the nature of learning in kindergarten emphasizes more fun learning activities so the concept of play is very strong, (2) children's activities in participating in science learning at Raudhatul Atfhal Asyyifa Medan showed a positive response in this case because learning is done while playing that brings children to a pleasant atmosphere because science experiments applied are varied experiments in which there are children's activities to think critically, and (3) the application of play methods can improve children's critical thinking skills in learning science.